2020
DOI: 10.1089/jop.2019.0135
|View full text |Cite
|
Sign up to set email alerts
|

Novel Ocular Drug Delivery Systems: An Update on Microemulsions

Abstract: Sufficient ophthalmic drug delivery is still challenging for pharmaceutical technologists, despite various scientific efforts. Several ocular drug carriers have been designed to enhance bioavailability by prolonging the drug retention time. One of the current encouraging approaches is the utilization of colloidal carriers with the characteristic submicron-nanometer size. Microemulsions (MEs) are such colloid systems that present sizes between 5 and 200 nm with significant thermodynamic stability and low surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(35 citation statements)
references
References 74 publications
0
31
0
1
Order By: Relevance
“…Several studies on this topic are reported in the literature [27][28][29][30][31]. Recently, a comprehensive review paper was published underlying that MEs could significantly play a major role in ocular disease treatments as they are easily handled and costeffective, but, up to today, applications found in the literature are still limited [32].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on this topic are reported in the literature [27][28][29][30][31]. Recently, a comprehensive review paper was published underlying that MEs could significantly play a major role in ocular disease treatments as they are easily handled and costeffective, but, up to today, applications found in the literature are still limited [32].…”
Section: Introductionmentioning
confidence: 99%
“…These ocular inserts can be provided from non-biodegradable and biodegradable materials. Non-biodegradable punctal plug delivery system (PPDS) can be made from polycaprolactum, hydroxyethyl methacrylate, and silicone that can present controlled drug release till 180 days [ 37 ]. PPDS proposes many advantages over topical drug delivery like patient compliance, decreasing the lacrimal drainage of drugs, capability of attaining controlled drug delivery, and possibly lower costs [ 38 ].…”
Section: Methods For Cornea Drug Deliverymentioning
confidence: 99%
“…Co-surfactant type and concentration in microemulsion considered for potential parenteral and ophthalmic administration should be also carefully chosen as some of them in higher amounts may cause pain upon injection or hemolysis and are not well tolerated by the eye [96]. However, despite the described difficulties, ocular and parenteral microemulsions are still extensively investigated and employed to obtain innovative drug delivery systems, like microemulsion-laden contact lenses [97][98][99].…”
Section: Applicationsmentioning
confidence: 99%